FIQH VS HADITH IN THE CONTEXT OF MOSQUES: A COMPARATIVE STUDY OF IMARAH MANAGEMENT - Mohammad Mas’ud Jauhari (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2024)
The purpose of this research is to explore: 1) the planning of fiqh and hadith studies at Al-Hikmah Mosque, 2) the implementation of fiqh and hadith studies at Al-Hikmah Mosque, 3) the evaluation of fiqh and hadith studies at Al-Hikmah Mosque. This research uses a qualitative approach with a descriptive method. The data sources for this study include the mosque chairman, the management of the imarah section, and the congregation of Al-Hikmah Mosque, obtained through interviews, observations, and documentation. The data collection techniques in this research are observation, interviews, and documentation. Meanwhile, the data analysis techniques used are data collection, data condensation, data presentation (data display), and conclusion drawing or verification.The results of this research conclude that: 1) The planning of fiqh and hadith studies at Al-Hikmah Mosque is carried out through small meetings or discussions with mosque management; 2) The implementation of fiqh and hadith studies at Al-Hikmah Mosque has been conducted well, and the mosque management provides the best facilities for the congregation to feel comfortable during religious studies. The fiqh study is led by Ustadz H. Awwab Ahmad Attamimi, and the hadith study is led by Ustadz H. Annas Said Azzo'bi, S.Pd.I.; 3) The evaluation of fiqh and hadith studies at Al-Hikmah Mosque is conducted through small meetings or informal discussions. After the evaluation, the mosque management must follow up to ensure that future religious studies are even better.